Different Transcriptional Profiles of Human Monocyte-Derived Dendritic Cells Infected with Distinct Strains of Mycobacterium tuberculosis and Mycobacterium bovis Bacillus Calmette-Guérin - Nunzia Sanarico; Alessia Colone; Manuela Grassi; Viviana Speranza; Daniela Giovannini; Antonio Ciaramella; Vittorio Colizzi; Francesca Mariani (Clinical and Developmental Immunology)
In order to analyze dendritic cells (DCs) activation following infection with different mycobacterial strains, we studied the expression profiles of 165 genes of human monocyte-derived DCs infected with H37Rv, a virulent Mycobacterium tuberculosis (MTB) laboratory strain, CMT97, a clinical MTB isolate, Mycobacterium bovis bacillus Calmette-Guérin (BCG), Aventis Pasteur, and BCG Japan, both employed as vaccine against tuberculosis. The analysis of the gene expression reveals that, despite a set of genes similarly modulated, DCs response resulted strain dependent. In particular, H37Rv significantly upregulated EBI3 expression compared with BCG Japan, while it was the only strain that failed to release a significant IL-10 amount. Of note, BCG Japan showed a marked increase in CCR7 and TNF-α expression regarding both MTB strains and it resulted the only strain failing in exponential intracellular growth. Our results suggest that DCs display the ability to elicit a tailored strain-specific immune response.